The antineoplastic properties of FTY720: Evidence for the repurposing of fingolimod - Patmanathan, S.N.; Yap, L.F.; Murray, P.G.; Paterson, I.C. (Wiley, 2015)

(untitled)
Almost all drugs approved for use in humans possess potentially beneficial off-target' effects in addition to their principal activity. In some cases this has allowed for the relatively rapid repurposing of drugs for other indications. In this review we focus on the potential for re-purposing FTY720 (also known as fingolimod, Gilenya), an immunomodulatory drug recently approved for the treatment of multiple sclerosis (MS). The therapeutic benefit of FTY720 in MS is largely attributed to the immunosuppressive effects that result from its modulation of sphingosine 1-phosphate receptor signalling. However, this drug has also been shown to inhibit other cancer-associated signal transduction pathways in part because of its structural similarity to sphingosine, and consequently shows efficacy as an anti-cancer agent both invitro and invivo. Here, we review the effects of FTY720 on signal transduction pathways and cancer-related cellular processes, and discuss its potential use as an anti-cancer drug.